New Insights into the Role of INSL-3 in the Development of Cryptorchidism - Alma-Raluca Lăptoiu; Elena-Lia Spoială; Gabriela Dumitrita Stanciu; Elena Hanganu; Vasile Valeriu Lupu; Carmen-Iulia Ciongradi; Cristina Gavrilovici (MDPI AG, 2023)
Cryptorchidism, defined as the failure of at least one or both testicles to descend into the scrotal pouches, is the most frequent (1.6-9% at birth, 1/20 males at birth) congenital anomaly encountered in newborn males, resulting in one of the most frequent causes of non-obstructive azoospermia in men. Similar to other congenital malformations, cryptorchidism is thought to be caused by endocrine and genetic factors, combined with maternal and environmental influences. The etiology of cryptorchidism is unknown, as it involves complex mechanisms aiming to control the testicular development and descent from their initial intra-abdominal location in scrotal pouches. The implication of insulin-like 3 (INSL-3) associated with its receptor (LGR8) is critical. Genetic analysis discloses functionally deleterious mutations in INSL3 and GREAT/LGR8 genes. In this literature review, we discuss and analyze the implication of INSL3 and the INSL3/LGR8 mutation in the occurrence of cryptorchidism in both human and animal models.